1982
DOI: 10.3168/jds.s0022-0302(82)82414-4
|View full text |Cite
|
Sign up to set email alerts
|

Absorption of Colostral Immunoglobulin G in the Newborn Dairy Calf

Abstract: Five groups of eight newborn calves were used to study absorption of colostral immunoglobulin G. One feeding of 2 liters of pooled colostrum was given at one of 6, 12, 24, 36, or 48 h after birth. Concentrations of immunoglobulin G in blood plasma and feces were measured by an immunodiffusion technique. Plasma volume and fecal excretion also were measured. When colostrum was given 6 h after birth, 65.8% of the ingested immunoglobulin G appeared in the plasma. This percentage declined rapidly to reach 46.9%, 11… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
61
0
2

Year Published

1998
1998
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(63 citation statements)
references
References 15 publications
0
61
0
2
Order By: Relevance
“…Others (13,14) also reported that PV increased as age increased to approximately 24 h because of the absorption of water and protein from the gut. Conversely, Matte et al ( 9 ) reported a decline in PV in calves fed colostrum at later ages. Estimates of PV declined from 14.5% of BW in calves that were initially fed colostrum at 6 h of age to 7.9% of BW in calves that were initially fed colostrum at 36 h of age.…”
Section: Resultsmentioning
confidence: 99%
“…Others (13,14) also reported that PV increased as age increased to approximately 24 h because of the absorption of water and protein from the gut. Conversely, Matte et al ( 9 ) reported a decline in PV in calves fed colostrum at later ages. Estimates of PV declined from 14.5% of BW in calves that were initially fed colostrum at 6 h of age to 7.9% of BW in calves that were initially fed colostrum at 36 h of age.…”
Section: Resultsmentioning
confidence: 99%
“…However, the transition of immunoglobulins obtained from colostrum takes place within a limited period of time. The small intestine of lambs begins to lose the ability to absorb maternal antibodies within 24-48 h after birth (8,9,11,13,14). The end of the intestinal wall permeability to macromolecules in newborn animals is called "intestinal closure" (4,15).…”
Section: Development Of the Neonatal Immune Systemmentioning
confidence: 99%
“…If the intake of antibodies from the colostrum is insufficient or absent, a significantly higher risk of morbidity or mortality exists (McGuire et al, 1976;Donovan et al, 1986;Rea et al, 1996). Because the calf's limited ability to consume a high volume at birth and IgG1 absorption from the intestine decreases significantly during the first 24 h (Matte et al, 1982), sufficient IgG concentration in the consumed colostrum of first milking is a prerequisite for the protective passive immune defense of the newborn calf.…”
mentioning
confidence: 99%